Halal assurance management system in chicken broiler industry - Ramli, Mohd Hasli; Rosman, Arieff Salleh; Khan, Aqeel; Ahmad Fadzillah, Nurrulhidayah; Hassan, Ahmad Muhyuddin; Samat @ Darawi, Abdul Basit; Saari, Zilal; Jandra, Mifedwil; Omar Jamil, Nor Azwa (Innovare Academics Sciences Pvt. Ltd, 2020)
Department of Islamic Development Malaysia (JAKIM) had made it compulsory for the application of Malaysia halal certificate at industry level to implement Halal Assurance System (HAS). The main purpose and focus to develop this halal system was to upgrade the integrity of halal product which was based by the 'Farm to Fork' concept that involved from the raw material production up to the end user in the chain. In the application of HAS, specifically in Malaysia the focus was only at the level of receiving of raw material until the end user, instead of started from the highest chain of food supply which involved the broiler chicken farm industry. Therefore, qualitative methodology through document analysis was used in order to obtain the source of information and to explain the element of HAS such as Halal Critical Point in broiler chicken farming activities. Other than that, issues related to the halal control such as animal feed, medication source and animal welfare also discussed in this paper to discover HAS application on farm level. This systematic system and halal certification policy will benefit on farming sector and make it able to be the main reference to halal player's integrity because it will give benefit the consumer from the whole of the halal food chain.